Clinical efficacy and safety of warm acupuncture in the treatment of type 2 diabetic kidney disease: A protocol of a randomized controlled trial. Issue 48 (2nd December 2022) - Gao, Yuancheng; Ji, Yue; Song, Yulin; Gong, Rui; Chen, Cheng; Chen, Hongbo
Abstract : Background: Type 2 diabetic kidney disease (DKD) is one of the most common and harmful chronic complications in clinical practice, and there is no reliable and targeted treatment plan at present. As a classic complementary and alternative therapy, evidence have shown that warm acupuncture has advantages in the treatment of type 2 DKD. However, there is still a lack of high-quality and long-term follow-up randomized controlled trials of warm acupuncture in the treatment of type 2 DKD. Methods: This is a prospective randomized controlled trial to investigate the efficacy and safety of warm acupuncture in the treatment of type 2 DKD. Participants will be randomly assigned in a 1:1 ratio to either the treatment group (treated with conventional Western medicine) or the control group (treated with warm acupuncture added on the basis of the control group). Both groups will receive 12 weeks of treatment followed by 24 weeks of follow-up. Observation indicators include: 24-hour urinary protein quantification, kidney function, TCM syndrome score and adverse reactions. Finally, SPSS21.0 software will be used to analyze the data. Discussion: This study will evaluate the efficacy and safety of warm acupuncture in the treatment of DKD, and the results of this trial will provide clinical evidence for the treatment of type 2 DKD. Trial registration: The TCTR identification number is TCTR20221104004.